Doping of TiO2 Using Metal Waste (Door Key) to Improve Its Photocatalytic Efficiency in the Mineralization of an Emerging Contaminant in an Aqueous Environment - Juárez Cortázar, Dany Edgar; Torres Torres, José Gilberto; Hernández Ramírez, Aracely; Arévalo Pérez, Juan Carlos; Cervantes Uribe, Adrián; Godavarthi, Srinivas; Espinosa de los Monteros, Alejandra Elvira; Silahua Pavón, Adib Abiu; Cordero García, Adrián (Molecular Diversity Preservation International, 2022)
Photocatalysis is an effective advanced oxidation process to mineralize recalcitrant contaminants in aqueous media. TiO2 is the most used photocatalyst in this type of process. To improve the deficiencies of this material, one of the most used strategies has been to dope TiO2 with metallic ions. Chemical reagents are often used as dopant precursors. However, due to the depletion of natural resources, in this work it was proposed to substitute chemical reagents and instead use a metallic residue (door key) as a doping precursor. The materials were synthesized using the sol–gel method and calcined at 400 °C to obtain the crystal structure of anatase. The characterization of the materials was carried out using X-ray diffraction (XRD), transmission electron microscopy (TEM), diffuse reflectance spectroscopy (DRS), scanning electron microscopy–energy-dispersive X-ray analysis (SEM-EDX) methods X-ray photoelectron spectroscopy (XPS), and inductively coupled plasma optical emission spectroscopy (ICP-OES). The results obtained indicate that Cu+/Cu2+ and Zn2+ ions coexist in the support, which modifies the physicochemical properties of TiO2 and improves its photocatalytic efficiency. The synergistic effect of the dopants in TiO2 allowed the mineralization of diclofenac in an aqueous medium when T-DK (1.0) was used as photocatalyst and simulated solar radiation as an activation source.